The Effect of Employee Competency on Employee Performance with Intrinsic Motivation as a Mediation Variable - Sana Rifatil Muna; Tetty Sufianty Zafar; Asep Muhamad Ramdan (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Business competition in the fashion retail sector requires companies to have employees with relevant competencies to achieve optimal performance. This study aims to analyze the effect of employee competency on employee performance with intrinsic motivation as a mediating variable. The study used a quantitative method with an explanatory approach. Data were collected through a Semantic Differential Scale questionnaire distributed to the entire population of 35 employees with a saturated sampling technique. Data analysis used Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4 software. The results of the study indicate that employee competency has a positive and significant effect on intrinsic motivation, intrinsic motivation has a positive and significant effect on employee performance, and intrinsic motivation is proven to fully mediate the effect of employee competency on employee performance, where the direct effect of competency on performance is not significant. These findings indicate that increasing employee competency does not automatically improve performance but must first stimulate intrinsic motivation. This research contributes to practical implications for companies in designing competency development strategies and strengthening employee intrinsic motivation.